Adsorption of hazardous dye Rhodamine B onto Brazilian natural bentonite. (2016) - Zimmermann, BÁ¡rbara Machado; Dotto, Guilherme Luiz; Kuhn, Raquel Cristine; Mazutti, Marcio Antonio; Treichel, Helen; Foletto, Edson Luiz
The potential of a Brazilian natural bentonite to remove Rhodamine B (RhB) dye from aqueous solutions was evaluated. The bentonite was characterised by X-ray diffraction, thermogravimetric analysis, particle size distribution and N2-adsorption isotherms. The adsorption of RhB onto bentonite was evaluated in batch system. The pH effect (2.5-10.5), kinetic curves and equilibrium isotherms (initial dye concentrations from 100 to 600 mg L −1 ) were studied at 25°C and 250 rpm. It was found that the Brazilian bentonite presented a mesoporous structure with surface area of 14.35 m 2 g −1 and average pore size of 28 nm. The adsorption capacity remained practically constant from pH 2.5 to pH 10.5. The Elovich model was adequate to represent the adsorption kinetic curves. Langmuir and Freundlich models were suitable to represent the adsorption isotherm. The maximum adsorption capacity was 77.3 mg g −1, obtained at 25°C, pH of 4.5 and adsorbent dosage of 500 mg L −1 . It was demonstrated that the Brazilian bentonite can be utilised as a promising adsorbent to remove RhB from aqueous solutions.